The ruling class of Judaea the origins of the Jewish revolt against Rome, A.D. 66 - 70 - Goodman, Martin 1953- (Cambridge Univ. Press, 1987)
This book examines why in AD 66 a revolt against Rome broke out in Judaea. It attempts to explain both the rebellion itself and its temporary success by discussing the role of the Jewish ruling class in the sixty years preceding the war and within the independent state which lasted until the destruction of the Temple in AD 70. The author seeks to show that the ultimate cause of the Revolt was a misunderstanding by Rome of the status criteria of Jewish society. The importance of the subject lies both in the significance of the history of Judaea in this period for the development of Judaism and early Christianity and in the light shed on Roman methods of provincial administration in general by an understanding of why Rome was unable to control a society with cultural values so different from its own